Las dos caras de la subversión: El caso de la prensa femenina en la Segunda República española - Gutiérrez Romero, María de los Ángeles (Sens public, 2021)
Within the study of the Spanish women's press, the magazines published during the Second Republic, until recently, have gone relatively unnoticed since they are rarely included in press history manuals. However, these magazines provide extraordinary information not only as documentary sources of daily life but as vehicles for subversive messages. In this sense, they even cover important news such as the rise of Nazism or they circumvent censorship to give voice to personalities with a belligerent anti-republicanism. One of the main themes will be the arrival of the “modern woman” prototype, which concentrates numerous debates around the aesthetic and behavioral transgression of women, which, in turn, becomes a representation of other topics such as family, nation or religion and whose perception in the articles is never absolute, but hinted at in the intense dialectic between tradition and modernity.